Eight‐type human papillomavirus E6/E7 oncoprotein detection as a novel and promising triage strategy for managing HPV‐positive women. Issue 1 (26th October 2018) - Rezhake, Remila; Hu, Shang‐Ying; Zhao, Shuang; Xu, Xiao‐Qian; Zhao, Xue‐Lian; Zhang, Li; Wang, Yan; Zhang, Xun; Pan, Qin‐Jing; Qiao, You‐Lin; Zhao, Fang‐Hui
Abstract : The management of HPV‐positive women becomes particularly crucial in cervical cancer screening. Here we assessed whether detection of E6 or E7 oncoproteins targeting eight most prevalent HPV types could serve as a promising triage option. Women (N = 1, 416) aged 50–60 from Shanxi, China underwent screening with HPV testing and liquid‐based cytology (LBC), with any positive results referring to colposcopy and biopsy if necessary. Women with HPV‐positive results received further tests using DNA‐based genotyping, E6 or E7 oncoprotein detection targeting HPV16/18 (for short: E6 (16/18) Test) or HPV16/18/31/33/35/45/52/58 (for short: E6/E7 (8 types) Test), respectively. Among HPV‐positive women, E6/E7 (8 types) oncoproteins had lower positivity (17.37%) compared to DNA‐based genotyping for same eight types (58.30%) and LBC with ASC‐US threshold (50.97%); HPV16 was the genotype showing the highest frequency (8.49%) for oncoprotein detection followed by HPV52 (3.47%), 58 (2.32%), 33 (1.54%), 18 (1.16%), 45 (0.77%), 35 (0.39%) and 31 (0%). For detection of cervical intraepithelial neoplasia Grade 3 or higher (CIN3+), E6/E7 (8 types) Test had similar sensitivity (100.00%) and superior specificity (85.94%) as well as positive predictive value (PPV, 22.22%) compared to both LBC and DNA‐based genotyping (8 types); For detection of CIN2+, E6/E7 (8 types) Test was less sensitive (67.74%) but still more specific (89.47%) and risk predictive with PPV of 46.67%. Notably, E6/E7 (8 types) Test remarkably decreased the number of colposcopies needed to detect one CIN2+ and CIN3+ (2.14 and 4.50). E6/E7 oncoprotein detection showed a good "trade‐off" between sensitivity and specificity with more efficient colposcopy referrals, which is of great importance to maximize the benefits of HPV‐based screening program, especially applicable for the areas with high HPV prevalence and low‐resources. Abstract : What's new? DNA‐based testing for human papillomavirus (HPV) is a sensitive method to detect HPV infection, but leads to considerable over referral and even overtreatment of HPV‐associated lesions. Here the authors expanded on a previously established DNA test specific for the E6 oncoprotein and showed better performance including higher predictive value of E6/E7 oncoprotein detection with inclusion of eight prevalent HPV types. Improved triage of HPV‐infected women is important especially in resource‐limited areas, helping to make HPV‐based screening programs economically feasible.